KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK BUBBLE PEARL TAPIOKA DAN PATI SAGU LOKAL KALIMANTAN BARAT - Y. Erning Indrastuti; Andreas Yolan Kristandi; Fenny Imelda (BPFP Faperta UNIB, 2023)
Sago starch from traditional industries in West Kalimantan has a sour aroma and brownish color, so it is only used to make traditional cakes. This study aimed to evaluate the physicochemical sensory characteristics of bubble pearl tapioca substituted for sago starch produced from a traditional industry in West Kalimantan. The results of this study are expected to diversify the use of local sago starch. Bubble pearls were made with various proportions of tapioca and sago starch (100:0 90:10 80:20 70:30%) and analyzed for water content, hardness, cooking loss, cooking time, rehydration capacity, and hedonic analysis (color, taste, aroma, and Springiness). The results showed that substituting sago starch in bubble pearls affected the water content, hardness, cooking loss, cooking time, rehydration capacity, color, and aroma of bubble pearls. Substitution of sago starch does not affect the taste and elasticity of the bubble pearls. A higher substitution of sago starch increased the bubble pearls' water content, hardness, and rehydration capacity. A higher substitution of sago starch decreased cooking loss, cooking time, color, and aroma of bubble pearl decreased. Sago starch from the local traditional industry of West Kalimantan can be used to substitute tapioca bubble pearls. However, panelists prefer bubble pearls from 100% tapioca in terms of color and aroma. Sago starch from the local industry has the potential to be used as bubble pearls by improving the color and aroma of sago starch.